Herpes simplex virus-induced cardiomyopathy successfully treated with acyclovir - Kuchynka, Petr; Palecek, Tomas; Hrbackova, Hana; Vitkova, Ivana; Simek, Stanislav; Nemecek, Eduard; Aster, Viktor; Louch, William E; Aschermann, Michael; Linhart, Ales (Wiener klinische Wochenschrift, 2010)
Inflammatory dilated cardiomyopathy (DCMi) represents an acquired form of dilated cardiomyopathy. Viral infection is the most common cause of DCMi. In contrast with other cardiotropic viruses, herpes simplex virus (HSV) is a very rare finding in endomyocardial biopsies of patients with dilated cardiomyopathy. We report a case of HSV-induced cardiomyopathy successfully treated with acyclovir.
Keywords: antivirové látky; Antiviral Agents; Cardiomyopathy, Dilated; dilatační kardiomyopatie; lidé středního věku; výsledek terapie; Male; Treatment Outcome; mužské pohlaví; Herpes Simplex; herpes simplex; Middle Aged; myokarditida; Myocarditis; Humans; lidé; Acyclovir; acyklovir